PROBLEMS IN THE IMPLEMENTATION OF THE MENTAL HEALTH LAW - DAVIS RURIK VAN ÑACA RAMIREZ (2020)
Currently there is a need to identify the problems that exist in society around their mental health and study the problems of the implementation of the Mental Health Law No. 30947 in Peru, because this will be a study of the Peruvian reality on The only way that allows us to propose improvements to the Law and formulate public and institutional policies at different levels of government. In this context, it is important to bring up a mention that our country is one of the group of States that have citizens who require preventive and welfare mental health care. But it also happens that curiously we are one of the countries with the least adapted infrastructure for these needs in hospitals, that's why there is the importance of deepening latent problems, without neglecting the team that works within these obligations to have adequate training for their work and having full knowledge of the rights that are in the sphere of patients. Thus, this study aims to address these problems related to the implementation of mental health in our country.